Kajian Keragaman Genetik Isolat Ralstonia solanacearum BIOVAR 3 menggunakan Penanda REP-PCR - Yadi Suryadi (Jurnal Perlindungan Tanaman Indonesia, 1999)
Study of DNA fingerprinting of genomic DNA of Australian Ralstonia solanacearum biovar 3 was characterized by a DNA BOX primer that correspond with repetitive sequence using PCR amplification (rep-PCR). Based on rep-PCR DNA profiles different band mobility were observed among Australian biovar 3. Most of isolates have shown common DNA amplification product at 600 bp. Cluster analysis to the DNA profiles showed two different DNA banding patterns that correlated with geographical origins of the isolates. Subgroup A correspond well with isolates from South Queensland/New South Wales, whilst subgroup B correspond with isolates from North Queensland origin.